Effectiveness of Antiseptic Liquid Smoke of Pine Fruit (Pinus merkusii) in Vitro and in Vivo - Alfani, Fhadliana; Armela, Diana Rizki; Adzra, Fa’izzah Nur; Fadhila, Feldha; Maryana, Yayan; Rumidatul, Alfi (Biomedika, 2022)
Hand sanitizers containing alcohol-based components are frequently used to clean hands due to their usage is more effective and efficient. Natural substances, such as pine fruit, can be used to replace alcohol-based components. Pine fruit may be processed into an antibacterial liquid smoke product, making it potentially useful as an antiseptic. The purpose of this research is to see how effective pine fruit liquid smoke is at inhibiting microbial growth in vitro and in vivo. In vitro disc diffusion test against E. coli ATCC 25922 and Staphylococcus aureus ATCC 25923, and employing disc and well diffusion methods on Aspergillus flavus ATCC 9643 and Candida albicans ATCC 10231. The pour plate approach was used in vivo. The in vitro test findings revealed an inhibitory zone on E. coli (5.3 mm) and S. aureus (5.83 mm) from 100% concentration of liquid smoke. The in vitro test results are supported by the in vivo test results, which indicate that the liquid smoke of pine fruit is 100% effective at preventing the growth of bacteria by 75.1% and fungi by 87.7%. The results of the questionnaire indicated that respondents liked the color (50%), and aroma (58%), that the product did not induce dryness (75%), and did not burning effects (83%). The result of this research is that 100% liquid smoke of pine fruit (Pinus merkusii) is effective in inhibiting the growth of E. coli ATCC 25922 and S. aureus ATCC 25923, as well as being effective as antiseptic agents.